PELAKSANAAN PROGRAM PERKEBUNAN DALAM PENGEMBANGAN PEREKONOMIAN MASYARAKAT - Fitriyani, Erna; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Abstract: In Plantation Programme Implementation Society for Economic Development. This study aims to determine the PIR program implementation in the village of Dayo and to determine the factors that affect the implementation of the PIR program Dayo village, subdistrict tandun, Rokan upstream. The research method used is a mixture of qualitative research quantitative type. Source data obtained from: The primary data source, which is localized through direct observation of program implementation PIR. The results of this study on the implementation of the PIR program experienced success Dayo village for 30 years and is a long-term development. The critical success factors derived from factor PIR implementation of communication, resources, disposition, and policy benefits.Keywords: Implementation of policy, Agriculture, Economics.